PENINGKATAN KEMAMPUAN MENGGUNAKAN PROBLEM FOCUSED COPING PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Siti Rohmah Nurhayati (Universitas Ahmad Dahlan, 2006)
Domestic Violence is a phernomenon that emphasize and paintful for the victims. Women victims of domestic violence up till now incline use emotion focused coping to face the violence. Utilizing of this strategy lean shackle them in the unended violence.The Women victims of domestic Â violence need to be empowered by improve their ability to use the problem focused coping. Violence is something that should be stopped, not to be tolerenced. One of the several manner to e dismissed it is by coping that directly interrelated with that violence.Theefforts can be done byhelping them to watch the violence causes in reality way, to restructurize a wrong conviction about cause of violence, and to improve their awareness of gender equality. There will be help them to appraise their self more positive and to influence them to select the coping more active and contructive.